Жанровая природа миниатюрной прозы : (На материале Стихотворений в прозе" И.С. Тургенева) - Полежаєва, Тетяна Вікторівна; Polezhaieva, Tetiana V. (Ленинградский государственный университет имени А.С. Пушкина, 2008)
В статье представлено ключевое значение сюжета в определении жанровой природы произведения, поэтика строения и развития сюжета миниатюрной прозы, композиционные возможности прозаических миниатюр «Стихотворений в прозе» И.С.Тургенева. У статті представлено ведуче значення сюжету у визначенні жанрової природи твору, поетика будови і розвитку сюжету мініатюрної прози, композиційні можливості прозаїчних мініатюр «Стихотворений в прозе» І.С.Тургенєва.

The article presents the key story in determining the nature of the genre works, poetics of structure and plot development of miniature prose composition possibilities of prose miniatures "Poems in Prose" by Ivan Turgenev. The article draws attention to the major causes of difficulties vopredelenii genre of art and offers an objective, a holistic picture of the actual system-genre of poetic principles structure and future developments and epic and lyric-epic thumbnails on thumbnails example Turgenev. The structure of the plot allocated: 1) large and medium genres (novels and stories), they have a great story (2nd and more storylines); 2) small and "very brief" genres, they have a small plot (a plot / storyline) with a simple structure of the plot - only those scenes and motifs, multiple or single. Further delineation of large genres of medium and small from the "very brief" is presented on a different basis - a typology of large or small plot, ie the presence of five classic stages: exposition, exposition, development of action, climax and denouement. The article discussed in detail about the delimitation by the development of small plot in small genres from a small plot in the "very brief" genres. Allocated a) The full development of the plot: see all these five steps, and b) the incomplete development of compressed: in the story verbally in stock is less than five stages: four, three, two or one. As an example, consider the different options genre miniatures "Poems in Prose" IS Turgenev. Commonly referred to as lyrical, but there are lyric-epic, epic with complete and incomplete development of their small plot.
Genre of miniature prose (based on «The poems in prose» I.S.Turgenev).
Keywords: жанр; сюжет; композиция; миниатюрная проза; стихи в прозе; И.С.Тургенев; genre; plot; composition; miniature; the poems in prose; I.S.Turgenev